2018
DOI: 10.1557/jmr.2018.397
|View full text |Cite
|
Sign up to set email alerts
|

Additive manufacturing-enabled shape transformations via FFF 4D printing

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 41 publications
1
56
0
Order By: Relevance
“…After the device is gently removed from the handling wafer, a slight amount of residual water underneath the device layer enables easy, smooth transfer (Figure b). Separately, an ABS film is prepared via ESP of transparent ABS filament (PLASIL, source material: LG Chem, ABS HI121H) through a heated nozzle (diameter: 0.4 mm; 230 °C) onto a glass substrate (120 °C) with a 3D printer (Sprout, Former's Farm) by the fused deposition method (the distance of the nozzle from the glass substrate = 0.1 mm and the ESP speed (υ ESP ) = 30 mm s −1 ) (Figure c); the ABS film prepared via ESP has residual stress due to the alignment of polymer chains . We note that the nozzle temperature was set to be the highest temperature within the feasible range (200–230 °C according to the datasheet from LG Chem) to obtain a film surface that is as smooth as possible.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the device is gently removed from the handling wafer, a slight amount of residual water underneath the device layer enables easy, smooth transfer (Figure b). Separately, an ABS film is prepared via ESP of transparent ABS filament (PLASIL, source material: LG Chem, ABS HI121H) through a heated nozzle (diameter: 0.4 mm; 230 °C) onto a glass substrate (120 °C) with a 3D printer (Sprout, Former's Farm) by the fused deposition method (the distance of the nozzle from the glass substrate = 0.1 mm and the ESP speed (υ ESP ) = 30 mm s −1 ) (Figure c); the ABS film prepared via ESP has residual stress due to the alignment of polymer chains . We note that the nozzle temperature was set to be the highest temperature within the feasible range (200–230 °C according to the datasheet from LG Chem) to obtain a film surface that is as smooth as possible.…”
Section: Resultsmentioning
confidence: 99%
“…This is because patterning via ESP on a stress‐free film generally induces residual shear stress and because transformation of the film is possible through an annealing process above the glass transition temperature ( T g ). The shape can be controlled by adjusting various parameters, such as the nozzle temperature, printing speed, printing pattern, porosity, and geometric dimensions (e.g., length, width, and thickness) . To the best of our knowledge, transformation examples at the electronics level via the indirect method have not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Rajkumar et al [ 48 ] reported the mechanisms that promote the thermally actuated shape-transformation in polylactic acid (PLA), high-impact-polystyrene (HIPS), and acrylonitrile-butadiene-styrene (ABS). Single-layer strips of different thermoplastics were tested at different speeds to assess the influence of printing speed on the shrinkage strain, and it was observed that higher printing speeds promote poor print quality.…”
Section: Shape Memory Effect In Polymersmentioning
confidence: 99%
“…It is an emerging technology where structures are printed layer by layer with the help of computer-aided design (CAD) models. Popular AM techniques include fused filament fabrication (FFF) [4,[10][11][12][13], selective laser sintering (SLS) [14,15], digital light processing (DLP) [16][17][18] and stereolithography (SLA) [19][20][21][22][23][24]. FFF has several advantages including simplicity of operation, lower cost of fabrication compared to conventional methods, e.g.…”
Section: Introductionmentioning
confidence: 99%